Information System Design at SMA Negeri 2 Linggo Sari Baganti Based on Web Server - Kevry Ramdany; Dio Hermanto; Sri Ardiyanti; Mezia Kemala Sari (Journal of Cyber Health and Computer, 2023)
The assessment system at SMAN 2 Linggo Sari Baganti still uses a grade book which is printed into the report card by each subject teacher. This allows errors to occur in entering grades into the report card. So a web-based assessment information system was designed that could help teachers in managing grades. The value data processing information system is a system that provides reporting information online to help speed up the delivery of information. The aim of creating this website is to build a grade information system that makes it easier to check, record, and report student grade data that can be accessed at any time. The information system was built using the PHP (Hypertext Preprocessor) language and MySQL (My Structured Query Language) database. The results of this research are in the form of an assessment website that can process data by teachers so that students can see the assessment results. Keywords— Database, MySQL, PHP, Sistem Informasi. Web Server